Dampak Faktor Non–Ekonomi Terhadap Perilaku Kepatuhan Pajak - Kusnadi, Siska; Maharani, Novera Kristianti (MES Management Journal, 2025)
This study was conducted with the aim of analyzing the impact of taxation knowledge, quality of tax authorities' services, taxpayer awareness and tax sanctions on the compliance of MSME taxpayers in Cakung Timur Village. The quantitative method is the type of research chosen in this study. Grand theory research uses attribution theory. This study uses primary data obtained from respondents' answers to statements given in the form of a questionnaire. The research population consists of all Micro, Small and Medium Enterprises (MSME) taxpayers registered at Jakpreneur under the guidance of the East Jakarta Small and Medium Enterprise Development Centre (PPUKM) Office, totaling 264 business actors. The sample of this study amounted to 73 respondents who were determined based on predetermined criteria, in other words the sampling method used was purposive sampling. Data analysis was conducted using SPSS 27 software. Data analysis was applied to descriptive statistics tests, test validity, test reliability, classical assumption tests for model suitability in tests (F test), this test section, (t) tests, and analysis with multiple linear regression. The results of this study indicate that the variables of tax knowledge, fiscal service quality, and tax payer awareness have a positive effect on tax compliance. On the other hand, tax sanctions have no effect on the level of taxpayer compliance.